2007
DOI: 10.1002/meet.1450440211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on trust perception and performance in computer‐mediated virtual environments

Abstract: An important area in Computer-Mediated Communication (CMC) is how gender affects trustbuilding and performance in virtual settings. This paper empirically investigates gender differences in two media, video and Instant Messaging, while performing negotiation tasks.The primary results indicate that: (1) female pairs perceive higher levels of trust than male pairs when gender information about the partner is either seen via the video channel or mutually revealed via the IM channel, and (2) male/female pairs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The qualitative analysis provides more detailed data to explain the results from our previous quantitative analyses, especially with respect to trust [4]. The higher levels of trust perceived by FF pairs in the VC and IM channels may be partly due to the conversational styles they used.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The qualitative analysis provides more detailed data to explain the results from our previous quantitative analyses, especially with respect to trust [4]. The higher levels of trust perceived by FF pairs in the VC and IM channels may be partly due to the conversational styles they used.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous paper [4], we reported the results of the quantitative analyses of trust and performance. First, we found that female pairs perceived higher levels of trust than male pairs when gender information was passively seen via the VC channel.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Females are more significantly affected by trust than males. Sun et al (2007), for example, point out that females achieve high levels of initial trust and perform better as well as willing to share information in computer-mediated virtual environments. Chan (2015) indicates that females' trust on social media platforms has a stronger effect in predicting online information sharing compared to males.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…The use of IM tools in various contexts has been studied extensively as well, e.g., in learning contexts (Wijekumar et al, 2005), in gaming environments, such as MMORPGs (Christopherson, 2010), and in virtual shared workspaces (Saparova et al, 2011). Prior studies have also looked at different variables that affect users' IM experiences, e.g., the effects of gender on trust perception and performance in CMC (Sun et al, 2007). In the past, the perceived usability of IM tools has been measured without differentiating between different communicators' task roles.…”
Section: Related Workmentioning
confidence: 99%